Implementation of extension services for children in Malaysian's public libraries: a case study / Mohd Shamsul Daud and Noryana Ahmad Khusaini - Daud, Mohd Shamsul; Ahmad Khusaini, Noryana (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Libraries are one of the best places to be visited by children during their leisure time. It is a place where they can get new information and knowledge through reading activity and to be seen as one excellent stop centre for children. But there will be very big challenges for library itself on how to maintain and ensure that the first time they came will never be the last one. This can be guaranteed by having extension services which will promise them with many exciting activities in library other than just reading activity. Implementing library extension services in Malaysia however is still not so huge in its practices. However, this could be very important issue to be discussed when the effectiveness of having those services will benefit many people. This research was done based on three (3) main objectives: (1) To Identify to what extent the implementation of the extension services at public libraries of northern region in Malaysia; (2) Seek factors that motivate and inhibit public library in providing extension services to the public and; {3} To identify the types of extension services suitable for children's mind development. This study uses qualitative methods, where four {4} directors of the public libraries in Northern region of Malaysia were interviewed to get their point of view towards this issue. Data obtained from this study had been analyzed using Atlas.ti software and three models were developed.